Leadership, Work Motivation, and Commitment's Impact on Work Discipline among Temanggung Regency's Public Junior High School Educators - Puspitasari, Merry Diana; Widiyanto, Widiyanto; Yusuf, Amin (Educational Management, 2022)
The goal of this research is to examine how teacher commitment mediates the relationship between leadership, job motivation, and professional discipline in the classroom. The success of a leader can be gauged by how well they carry out their many duties, such as making plans, enforcing those plans, and overseeing their employees. A teacher's effectiveness is influenced by their leadership, their work drive, and their dedication to their profession. This study employed a quantitative approach to research. To conduct this research, 92 educators from Temanggung district's public junior high schools participated. The data was collected using a cluster proportional sampling method. Before being employed in the study, the questionnaire underwent rigorous validity and reliability testing. Path analysis and the Sobel test were utilized to examine potential mediating variables in the data analysis for hypothesis testing. Leadership, workplace motivation, and teacher dedication were proven to have an impact on classroom performance. Leadership and employee motivation were mediated by teachers' dedication to their profession. The result is that instructor dedication to discipline can dampen the impact of the independent variables on the dependent variable.